Nutritional Evaluation of Quince Fruit and its Products - Sangita Sood and Mrinalini Bhardwaj (Journal of Krishi Vigyan, 2015)
An effort was made to evaluate the Quince fruit for its quality parameters and develop products namely pickle, preserve, jam, chutney , squash, RTS and candy. The different products were evaluated for various chemical constituents. On an average, it was founded that these products are well suited for table use as they are rich in various constituent especially fiber and low in fat content i.e. almost equivalent to zero. So such product can find their remedial use in various health related diseases